The Effects of Mega-Herbivore Extinctions on Seed Dispersal and Community Structure in An East African Savanna - Bernard, Miranda; Booth, Laura; Kielar, Abraham (Consilience, 2015)
Herbivory is a prominent top-down force shaping the landscape of semi-arid savannas in East Africa. Herbivores participate in seed dispersal both by ingesting and defecating the seeds of endozoochorously-dispersed plants and by translocating the seeds of exozoochorously-dispersed plants. In this study, we sought to determine how the extinction of large mammalian herbivores would affect the abundance of five focal species of plants that use fruiting as theira primary dispersal mechanism. We also examined how the absence of large mammalian herbivores affected seed predation by small mammals. We counted the number of individual plants for each of the five species in three short-term (5 yearr. old) exclusion blocks and one long-term (15 yearr. old) exclusion block. We found that total abundance of fleshy-fruited species increaseds as successive levels of large mammalian herbivores weare excluded and as the duration of herbivore exclusion increaseds. Within species, we found that C. orthacantha and S. campylacanthum increased in the absence of herbivores, while O. stricta decreased in the absence of herbivores. B. aegyptiaca and B. albitrunca did not exhibit differences in abundance between different levels of herbivore exclosure. We found that small mammals demonstrated a preference for B. albitrunca and O. stricta seeds, which were consumed primarily by the fringe-tailed gerbil, Gerbilliscus robustus. Understanding the interactions between herbivores and vegetation is vital to conserving understanding how plant communities as well as understanding how they may change in the future, as well as how to conserve them.